Patient journey following lumbar discectomy surgery: protocol for a single-centre qualitative analysis of the patient rehabilitation experience (DiscJourn) - White, Louise (BMJ Open, 2019)
INTRODUCTION: Lumbar discectomy is a widely used surgical procedure internationally with the majority of patients experiencing significant benefit. However, approximately 20% of patients report suboptimal functional recovery and quality of life. The impact and meaning of the surgical experience from the patients’ perspective are not fully understood. Furthermore, there is limited evidence guiding postoperative management with significant clinical practice variation and it is unclear if current postoperative support is valued, beneficial or meets patients’ needs and expectations. This study aims to address the evidence gap by moving beyond current knowledge to gain insight into the lived experiences relating to patients’ lumbar discectomy surgery journey. Results will inform more meaningful and specific care, thus, enhance rehabilitation and outcomes. METHODS AND ANALYSIS: A qualitative investigation using interpretative phenomenology analysis (IPA) will provide a flexible inductive research approach. A purposive sample (n=20) of patients undergoing primary discectomy will be recruited from one UK NHS secondary care centre. Semi-structured interviews will be conducted postsurgery discharge. A topic guide, developed from the literature and our previous work with input from two patient co-investigators, will guide interviews with the flexibility to explore interesting or patient-specific points raised. Providing longitudinal data, patients will keep weekly diaries capturing experiences and change over time throughout 12 months following surgery. A second interview will be completed 1 year postsurgery with its topic guide informed by initial findings. This combination of patient interviews and diaries will capture patients’ attitudes and beliefs regarding surgery and recovery, facilitators and barriers to progress, experiences regarding return to activities/function and interactions with healthcare professionals. The rich density of data will be thematically analysed in accordance with IPA, supported by NVivo software. ETHICS AND DISSEMINATION: Ethical approval has been granted by the London-Bloomsbury Research Ethics Committee (18/LO/0459; IRAS 241345). Conclusions will be disseminated through conferences and peer-reviewed journals.